PERILAKU HIDUP BERSIH DAN SEHAT PEDAGANG DI PASAR TANJUNG ANYAR KOTA MOJOKERTO TAHUN 2015 - Dwi Okta Vania Sari; Sri Mardoyo; Sudjarwo . (GEMA LINGKUNGAN KESEHATAN, 2015)
Promotion of Clean and Healthy Behavior (CHB) in public places constitutes an effort to empower the community, buyers and the management of public places to be aware of, willing andable to practice CHB an play an active role in creating healthy public places, sucs as markets.  The study was descriptive. Data were collected by interviews, questionnaires and observations. A sample consisting of 95 merchants was taken. Data were analyzed descriptivelyand tabulated and summarized Results showed that 57,6% of the sample indicated that the market’s sanitation facilitieswere poor. Results of assessment of the level of knowledge showed that 74,7% (71) and 25,3% (24) of the sample had good and adequate knowledge of clean and healthy behavior, respectively.Furthermore, 100% (95) of the merchants had good attitudes. Additionally, 45,3% (43) of themerchants had the required action and 54,7% (52) had not. In conclusion, the market’s sanitation facilities did not meet the requirements for marketsas defined by Decree of the Minister of Health of the Repubilc of Indonesia No. 519/Menkes/SK/VI/2008 regarding Guidelines for Implementation of a Healthy Market. The market management is recommended to improve the components of sanitation facilities that do not meetthe requirements and socialize clean and healthy behavior in the market.